Hydrogen Sulfide Is an Endogenous Regulator of Aging in Caenorhabditis elegans - Qabazard, Bedoor (Mary Ann Liebert, Inc., 2014)
Aims: To investigate the role of endogenous hydrogen sulfide (H(2)S) in the control of aging and healthspan of Caenorhabditis elegans. Results: We show that the model organism, C. elegans, synthesizes H(2)S. Three H(2)S-synthesizing enzymes are present in C. elegans, namely cystathionine γ lyase (CSE), cystathionine β synthetase, and 3-mercaptopyruvate transferase (MPST or 3-MST). Genetic deficiency of mpst-1 (3-MST orthologue 1), but not cth-2 (CSE orthologue), reduced the lifespan of C. elegans. This effect was reversed by a pharmacological H(2)S donor (GYY4137). GYY4137 also reduced detrimental age-dependent changes in a range of physiological indices, including pharyngeal contraction and defecation. Treatment of C. elegans with GYY4137 increased the expression of several age-related, stress response, and antioxidant genes, whereas MitoSOX Red fluorescence, indicative of reactive oxygen species generation, was increased in mpst-1 knockouts and decreased by GYY4137 treatment. GYY4137 additionally increased the lifespan in short-lived mev-1 mutants with elevated oxidative stress and protected wild-type C. elegans against paraquat poisoning. The lifespan-prolonging and health-promoting effects of H(2)S in C. elegans are likely due to the antioxidant action of this highly cell-permeable gas. Innovation: The possibility that novel pharmacological agents based on the principle of H(2)S donation may be able to retard the onset of age-related disease by slowing the aging process warrants further study. Conclusion: Our results show that H(2)S is an endogenous regulator of oxidative damage, metabolism, and aging in C. elegans and provide new insight into the mechanisms, which control aging in this model organism. Antioxid. Redox Signal. 20, 2621–2630.